Comparative Profiling of Survival, Growth, and Intestinal Microbial Community of Pearl Oyster Pinctada maxima Juvenile in the Industrial Farming: The Feasibility of Using Spray-Dried Microalgae Powder - Yang, Shouguo; Li, Xi; Vasquez, Hebert Ely; Wang, Aimin; Shi, Yaohua; Li, Jiaoni; Zhang, Xingzhi; Zheng, Xing; Gu, Zhifeng (Frontiers in Marine Science, 2022)
Industrial farming is an alternative mode for Pinctada maxima juvenile cultivation to avoid mass mortality caused by natural disasters. Suitable and enough food is crucial for successful industrial bivalve farming. To investigate the feasibility of live microalga instead of spray-dried microalgal powder in P. maxima juvenile industrial farming, this study replaces a positive control live microalgal diet [Isochrysis zhanjiangensis (L-iso) and Platymonas subcordiformis (L-pla)] with spray-dried I. zhanjiangensis powder (P-iso) and P. subcordiformis powder (P-pla). Continuous feeding trials (30 days) were conducted on the P. maxima juvenile (1.2008 ± 0.0009 g initial weight and 30.12 ± 0.05 mm initial shell length), under laboratory conditions. Survival, growth performance, and intestinal microbial community were studied and compared across the groups. Results showed that survival rate (SR) did not differ significantly across the groups (ranged from 84 to 86%, P > 0.05). The growth performance in spray-dried microalgal groups, including total weight (TW), shell height (SH), absolute growth rate (AGR), and relative growth rate (RGR) for SH and TW, was slightly lower than that in live microalgal groups, while the activities of pepsin (PES), amylase (AMS), and lipase (LPS) were significantly higher (P < 0.05). The best growth performance was observed in the L-iso group, followed by the L-pla group. A 16S rRNA-based sequencing revealed that Proteobacteria was the dominant phylum in P. maxima juvenile intestinal bacterial community under controlled conditions, which accounted for 62–82% across groups. The intestinal bacteria at the genus level were more sensitive to diets, whereas Burkholderia was the dominant genus in both L-iso (66.52 ± 6.43%) and L-pla groups (54.00 ± 5.66%), while Mycoplasma, Alphaproteobacteria, and Oxyphotobacteria were in both P-iso and P-pla groups. The P-pla group got higher ACE, Chao1, and Simpson and Shannon indices (P < 0.05). The above results suggested that the spray-dried P-iso and P-pla can serve as substitutes for live microalga in P. maxima juvenile industrial farming under controlled conditions. The finding in this study provides basic data to optimize industrial farming technology and healthy management for P. maxima juvenile.